Effective Learning Strategies in The Emergency Department for Medical Students - Imamul Aziz Albar; Ardi Findyartini (eJournal Kedokteran Indonesia, 2023)
Clinical learning in the emergency department is one of the rotations carried out by medical students in the medical education program. Learning in the emergency department can help students fulfill their competence in emergency clinical skill, such as basic life support, management of acutely ill patients and some other competencies. However, the emergency department has some limitations, such as the variety of professionals and students serving the patients, various diseases with varying levels of severity, as well as the unpredictable condition and number of patients. Those reasons make it difficult for students to study and practice emergency medicine well. Therefore, clinical educators’ awareness of the conditions in the emergency department and the application of appropriate learning models will enable students to get the best learning experience in the emergency department.